The Relationship Between Self-Esteem and Academic Achievement of Girls with Hearing Impairments in Secondary Schools for the Deaf in Kenya - Awori, Beatrice Bunyasi; Mugo, John K.; Orodho, John A.; Karugu, G. K. (Journal of the American Academy of Special Education Professionals, 2010)
Several factors had been cited as contributing to the perpetually dismal academic achievement of girls with hearing impairment in Kenya. Personal esteem factors had not been adequately explored. The study used Carl Roger’s client-centered theory and an Expost facto design. Rosenberg self-esteem scale was used to measure self-esteem dimensions. School academic scores were used to measure academic achievement. A sample of fifty-three girls was drawn. Data were collected through questionnaires and interviews. The results: girls with hearing impairment possessed positive/high self-esteem but academic achievement was low. It was concluded that girls with hearing impairment placed more value on relational aspects (grooming), music and dance. They lagged behind due to lack of specialized technological devices. The study recommended: teachers to make deliberate use of positive reinforcement; principals to initiate active collaborations with interested partners; the government to make the curriculum more flexible and curriculum developers to reconsider curricula adaptation. Kenya National Examination Council to focus on practical assessment and/or use of sign language interpreters. The government to increase disability fund and provide opportunities for capacity building for assistive-devices-technicians. Further research in the area of teachers’ proficiency in Kenya Sign Language to be conducted.